Evaluation of Vaccine Stock Management at the Karanganyar Regency Health Service Indonesia - Kurniawan, Andre; Jason Merari Peranginangin; Samuel Budi Harsono (Open Access Indonesian Journal of Medical Reviews, 2024)
Vaccines are very susceptible to damage, so vaccine management requires special handling, this is done to maintain vaccine quality. The aim of this research is to find out the description and evaluate suitability vaccine management at the Karanganyar Regency Health Service (DKK) in 2022 based on Minister of Health Regulation No. 12 of 2017. This research is a qualitative descriptive non-experimental research. These research methods cross sectional by using approach, observation or data collection. The sampling technique uses accidental sampling by reviewing and evaluating vaccine management, which includes planning, procurement, receipt, storage, and distribution at the Karanganyar Health Service. The method used for data collection uses checklist suitability and in-depth interviews with the Head of Installation and pharmacy officers. Vaccine planning is adjusted to the usage index and needs in the previous year using a combined method system top to bottom and bottom up. Vaccine procurement is centralized at the Provincial Health Service, where requests are made by method bottom up. Receiving the vaccine is not immediate drop from the center/province, but the Karanganyar DKK takes the needed vaccines to the Provincial Health Service using the provisions for good drug distribution methods. Vaccine storage and distribution at DKK Karanganyar is in accordance with Minister of Health Regulation number 12 of 2017 and also in accordance with vaccine management guidelines from the Ministry of Health in 2021. Vaccines at DKK Karanganyar are in accordance with Minister of Health Regulation number 12 of 2017 and also in accordance with vaccine management guidelines from the Ministry of Health in 2021, both in planning, procurement, receipt, storage and distribution.